RESEARCH ON CORPORATE INTERNATIONAL SOCIAL RESPONSIBILITY REPORTING OF CHINESE INTERNATIONAL ENTERPRISES’ IN KAZAKHSTAN - Zhantore Ulsara Nematullakyzy; Zhou Xiao Hu (Scientific Journal of Pedagogy and Economics, 2021)
The paper investigates about corporate international social responsibility’s (CISR) disclosure to examine the reporting content about overseas markets of Chinese international enterprises’ (CIE) in Kazakhstan. The purpose is to explore the level of CISR developments and international social contributions of CIE. In this study has been applied stakeholder theory to analyse and categorize CISR, we put ours emphasizes on environmental, human resource, community, productive, political and other activities. It is across-sectional study which has exploratory in nature and involved in a secondary data collection and used of content analysis technique to assess the statistical results. International enterprises with higher levels of CISR activities are more likely to be internationalized and capable of establishing in the international business network. The results indicated that CISR’s political activity of the CIEs’ have not been issued in annual reports. Moreover, the other CISR activities are in a gradually improving on various degree. This study contributes to stakeholder theory and CISR research in the international business field, implications for implementing the level of CISR activities.